Optimisation and establishment of diagnostic reference levels in paediatric plain radiography - Paulo, Graciano do Nascimento Nobre (2016)
Tese de doutoramento em Ciências da Saúde, no ramo de Tecnologias da Saúde, apresentada à Faculdade de Medicina da Universidade de Coimbra